2006
DOI: 10.1124/mol.106.026567
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of Action of 9-O-Arylalkyloxime Derivatives of 6-O-Mycaminosyltylonolide, a New Class of 16-Membered Macrolide Antibiotics

Abstract: New 16-membered 9-aryl-alkyl oxime derivatives of 5-O-mycaminosyl-tylonolid (OMT) have recently been prepared and were found to exhibit high activity against macrolide-resistant strains. In this study, we show that these compounds do not affect the binding of tRNAs to ribosomes in a cell-free system derived from Escherichia coli and that they cannot inhibit peptidyltransferase, peptidyl-tRNA translocation, or poly(U)-dependent poly(Phe) synthesis. However, they severely inhibit poly(A)-dependent poly(Lys) synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 37 publications
3
24
0
2
Order By: Relevance
“…In saturation binding experiments, [ 14 C]erythromycin readily bound to ribosomes from both bacteria, exhibiting dissociation constants (K d s) of 66 Ϯ 11 nM and 11 Ϯ 1 nM for the E. coli and S. aureus ribosomes, respectively (data not shown). These values were comparable to those previously published (10 Ϫ8 to 10 Ϫ7 M) (8,19). Binding of erythromycin saturated close to 1 pmol of the drug per 1 pmol of E. coli or S. aureus ribosomes, indicating that the majority of the ribosomes in the preparation were competent for binding.…”
Section: Affinity Of Cem-101 To Wild-type Ribosomes From E Coli and supporting
confidence: 79%
“…In saturation binding experiments, [ 14 C]erythromycin readily bound to ribosomes from both bacteria, exhibiting dissociation constants (K d s) of 66 Ϯ 11 nM and 11 Ϯ 1 nM for the E. coli and S. aureus ribosomes, respectively (data not shown). These values were comparable to those previously published (10 Ϫ8 to 10 Ϫ7 M) (8,19). Binding of erythromycin saturated close to 1 pmol of the drug per 1 pmol of E. coli or S. aureus ribosomes, indicating that the majority of the ribosomes in the preparation were competent for binding.…”
Section: Affinity Of Cem-101 To Wild-type Ribosomes From E Coli and supporting
confidence: 79%
“…We have previously demonstrated that 16-membered macrolides, like tylosin, inhibit AcPhe-puromycin synthesis, whereas 14-membered macrolides, such as erythromycin, do not (7,16). This is due to the fact that the C-5-disaccharide of tylosin reaches into the peptidyl transferase (PTase) center of the ribosome, whereas the C-5-monosaccharide of 14-membered macrolides is too short (3,13,32,37).…”
Section: Vol 53 2009mentioning
confidence: 85%
“…The initiation inhibitor edeine inhibited both poly(Phe) and poly(Lys) synthesis, as reported previously (8). The differential effects of macrolides on poly(Phe) and poly(Lys) synthesis have been observed previously (16,36). One possible explanation for the lack of inhibitory effect of macrolides on poly(Phe) synthesis is that the highly hydrophobic nascent poly(Phe) chain may displace K-1325 from its binding site on 50S subunits as it passes through the tunnel.…”
Section: Vol 53 2009mentioning
confidence: 96%
“…This type of competition can follow two alternative mechanisms, as depicted in Schemes 2 and 3. Kinetic equations concerning Schemes 2 and 3 have been derived in previous publications 19,20 , and the main functions are presented in Table 1. Plotting our data to these equations gives us the opportunity to distinguish, which of the two mechanisms is followed by K-1602.…”
Section: Competition Of K-1602 and Tylosin For Binding On The Ribosommentioning
confidence: 99%
“…Following detailed kinetic analysis, we determined the association and dissociation constants of K-1602 with the ribosome. Calculations were based on a previously developed kinetic model [19][20][21] , which allowed us to conclude that K-1602 behaves as a slow binding slowly dissociating inhibitor 22 , thus explaining the unique characteristics and effectiveness of this compound. Slow binding inhibitors represent a large kinetic class, mainly including transition state and reaction intermediate analogs, and as such show promising features for future drug development 23 .…”
Section: Introductionmentioning
confidence: 99%